C60/graphene/g-C3N4 composite photocatalyst and mutually- reinforcing synergy to improve hydrogen production in splitting water under visible light radiation. Issue 10 (July 2017) - Song, Limin; Guo, Caiping; Li, Tongtong; Zhang, Shujuan
Abstract: g-C3 N4 as a new metal-free photocatalytic material for water splitting has attracted much attention in recent years, but its photocatalytic efficiency needs further improvement. Here we synthesized novel C60 /graphene/g-C3 N4 composite photocatalytic materials with high hydrogen generation ability for water splitting under visible light radiation (λ>420 nm). These materials take full advantage of the electron conduction expressing of graphene and the superior-strong electron-attracting ability of C60 . The mutually-reinforcing synergy between graphene and C60 improves the migration and utilization efficiency of photo-generated electrons and accelerates the separation of photo-generated charges, thus significantly enhancing the hydrogen generation capacity of g-C3 N4 . The hydrogen production amount and rate of C60 / graphene/g- C3 N4 (10 mg/L C60 and graphene) after 10 h are 5449.5 µmol/g and 545 µmol/g/h, which is 539.6 times of pure g-C3 N4 under the same condition. The values are 50.8 and 4.24 times of graphene/g-C3 N4 (10 mg/L graphene) and C60 /g-C3 N4 (10 mg/L C60 ), respectively. The apparent quantum yield of C60 /graphene/g- C3 N4 (10 mg/L C60 and graphene) in 97 h is about 7.2%. The improvement of hydrogen generation activity in 97 h suggests the high long-time stability of C60 /graphene/g- C3 N4 in photocatalytic water spitting. The photocatalytic ability of C60 /graphene/g- C3 N4 can be controlled by regulating the addition of graphene and C60 . The mutually-reinforcing synergy between graphene and C60 was proved by X-ray photoelectron spectroscopy, photoluminescence spectrum and organic electron acceptors of MV 2+ . Thus, the joint action of C60 and graphene promotes the migration, separation and utilization of photo-generated electrons, which is responsible for the significant enhancement of photocatalytic performance.